Adenosine A2A Receptor Deficiency Alleviates Blast-Induced Cognitive Dysfunction. Issue 11 (November 2013) - Ning, Ya-Lei; Yang, Nan; Chen, Xing; Xiong, Ren-Ping; Zhang, Xiu-Zhu; Li, Ping; Zhao, Yan; Chen, Xing-Yun; Liu, Ping; Peng, Yan; Wang, Zheng-Guo; Chen, Jiang-Fan; et al.
Traumatic brain injury (TBI), particularly explosive blast-induced TBI (bTBI), has become the most prevalent injury among military personnel. The disruption of cognitive function is one of the most serious consequences of bTBI because its long-lasting effects prevent survivors fulfilling their active duty and resuming normal civilian life. However, the mechanisms are poorly understood and there is no treatment available. This study investigated the effects of adenosine A2A receptor (A2AR) on bTBI-induced cognitive deficit, and explored the underlying mechanisms. After being subjected to moderate whole-body blast injury, mice lacking the A2AR (A2AR knockout (KO)) showed less severity and shorter duration of impaired spatial reference memory and working memory than wild-type mice did. In addition, bTBI-induced cortical and hippocampal lesions, as well as proinflammatory cytokine expression, glutamate release, edema, cell loss, and gliosis in both early and prolonged phases of the injury, were significantly attenuated in A2AR KO mice. The results suggest that early injury and chronic neuropathological damages are important mechanisms of bTBI-induced cognitive impairment, and that the impairment can be attenuated by preventing A2AR activation. These findings suggest that A2AR antagonism is a potential therapeutic strategy for mild-to-moderate bTBI and consequent cognitive impairment.